2020
DOI: 10.21203/rs.3.rs-81476/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Investigation of the Relationship Between the Inherited Thrombophilia and Novel Coronavirus Pneumonia

Abstract: Purpose: Novel coronavirus pneumonia (NCP) is a disease caused by severe acute respiratory syndrome coronavirus 2 virus. It was reported that there is a relationship between severe NCP and hypercoagulable conditions that predispose patients to thrombosis. Thrombophilia is a multifactor condition that can result from genetic factors, acquired factors, or a combination of both. The prothrombin gene (F2 rs1799963 known as G20210A), Factor V Leiden (F5 rs6025 known as G1691A) and PAI-1 (rs1799768) are important po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Many studies have found associations between hereditary thrombophilia factors (FVL, PAI‐1, etc.) and thromboembolic disease, which is common in severe novel coronavirus pneumonia (NCP; COVID‐19) and often associated with death, 13,31 while other have not 15 . In a study of autopsy patients, investigators found no association with inherited thrombophilia factors (FII and FVL) in patients with thromboembolism 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found associations between hereditary thrombophilia factors (FVL, PAI‐1, etc.) and thromboembolic disease, which is common in severe novel coronavirus pneumonia (NCP; COVID‐19) and often associated with death, 13,31 while other have not 15 . In a study of autopsy patients, investigators found no association with inherited thrombophilia factors (FII and FVL) in patients with thromboembolism 12 …”
Section: Discussionmentioning
confidence: 99%
“…It is important to monitor the prognosis in patients with COVID‐19 and to identify patients at high risk of thrombosis in the post‐COVID period. Although there are studies in the literature trying to reveal the relationship between COVID‐19 hereditary thrombophilia factors, 12–16 there is no study examining the relationship between hereditary thrombophilia and COVID‐19 in patients with high thrombosis risk. Demonstrating this relationship may facilitate the follow‐up of COVID‐19 patients in terms of clinical progression and enable appropriate treatment to be initiated in the early period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there is no study in the literature investigating the effect of hereditary thrombophilia on the course of COVID-19, except for a few studies with limited series of patients. In the bibliographic analysis obtained from PubMed (January 2022) regarding genetic thrombophilia and clinical outcomes in COVID-19 disease, one case report and two studies with smaller patient samples were seen [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be hypothesized that FVL and PTGM mutations deteriorate the clinical outcome, especially with thrombotic complications, of the patients with COVID-19. Upon examining studies investigating the relation between genetic thrombophilia and clinical outcomes in COVID-19, especially with its thrombotic complications, few examples were found in the literature (one case report and two studies with smaller patient samples) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%